2022
DOI: 10.1021/acsnano.2c01968
|View full text |Cite
|
Sign up to set email alerts
|

Piezotronic Effect-Augmented Cu2–xO–BaTiO3 Sonosensitizers for Multifunctional Cancer Dynamic Therapy

Abstract: Ultrasound (US)-triggered sonodynamic therapy (SDT) based on semiconductor nanomaterials has attracted considerable attention for cancer therapy. However, most inorganic sonosensitizers suffer from low efficiency due to the rapid recombination of electron–hole pairs. Herein, the Cu2–x O–BaTiO3 piezoelectric heterostructure was fabricated as a sonosensitizer and chemodynamic agent, simultaneously, for improving reactive oxygen species (ROS) generation and cancer therapeutic outcome. Under US irradiation, the Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 52 publications
0
83
0
Order By: Relevance
“…TME greatly affects the efficacy of nanomaterials, one exception are Cu(I)-based nanoparticles which are more versatile in weakly acidic environments and actually give high ·OH yield [ 7 ]. The reaction rate of Cu(I) based Fenton reaction is much greater than that of Fe-based Fenton reaction [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…TME greatly affects the efficacy of nanomaterials, one exception are Cu(I)-based nanoparticles which are more versatile in weakly acidic environments and actually give high ·OH yield [ 7 ]. The reaction rate of Cu(I) based Fenton reaction is much greater than that of Fe-based Fenton reaction [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group designed and fabricated the Cu 2-x O-BTO piezoelectric heterostructure as a sonosensitizer for the combination of SDT and chemodynamic therapy (CDT) against cancer (Figure 4a). [91] When Cu 2-x O-BTO was activated by US stimulation, the polarized piezoelectric [107] The in vivo experiments also demonstrated that the combination of SDT and CDT achieved potent tumor inhibition in 4T1 tumor-bearing mice (Figure 4b). It is noteworthy that the CDT efficacy can be further promoted with the assistance of US through electron lever strategy due to the increased electron density of the active sites in the piezoelectric perovskite nanocrystals.…”
Section: Perovskite Nanomaterialsmentioning
confidence: 95%
“…As a kind of classical perovskites nanomaterial, asymmetric tetragonal BaTiO 3 nanoparticles (T-BTO NPs) can establish a dynamic built-in electric field under US vibration, by which the separation of e − and h + occurred continuously to trigger redox reactions and produce ROS. [90][91][92] Inspired by the piezoelectric effect, Zhu et al prepared T-BTO NPs with a diameter of 106.91 � 49.72 nm via a typical hydrothermal method, which was used as a new kind of sonosensitizer for cancer SDT. [90] The results of electron spin resonance (ESR) demonstrated that T-BTO aqueous solution showed distinct •OH and •O 2 − characteristic signals under US irradiation, while no significant radical signal was detected in the mere T-BTO or US groups.…”
Section: Perovskite Nanomaterialsmentioning
confidence: 99%
“…It is found that SDT is similar to photocatalytic oxidation, and the difference is just irradiation conditions. Inspired from photocatalysis, sonosensitizers with narrow band gaps are considered as candidates to increase the number of generated charges. , Besides the construction of heterostructures, the addition of scavengers is also an effective approach to inhibit electron–hole recombination to enhance catalytic performance. Considering the complexity of the tumor microenvironment (TME), it is more likely to use some intracellular constituents as scavengers, such as endogenous glutathione (GSH), to decrease the risk of side effects from other additives.…”
Section: Introductionmentioning
confidence: 99%